The PICU Book : a Primer for Medical Students, Residents and Acute Care Practitioners - Perkin, Ronald M.; Fiordalisi, Irma; Novotny, William E. (World Scientific Pub. Co., 2012)
This book is a clinical guide in the practice of pediatric critical care and can serve as a roadmap for an introductory journey through this broad and challenging subspecialty. Key topics intrinsic to the practice of pediatric critical care are addressed from an organ-system and disease-specific perspective, and tailored to the needs of new learners. Comprehensive, practical and up-to-date information is provided in a user-friendly format that facilitates both learning and care implications. Each topic is analyzed and discussed in a custom-built section to provide both an overview and the necessary detail to help the reader participate in and contribute to patient care. Definitions, etiologies, physical findings, laboratory and radiologic data, differential diagnoses, management, suggested consultations and prognosis are condensed using easy-to-find boxes, bulleted lists, decision trees, tables and illustrations.